1989
DOI: 10.1207/s15516709cog1302_1
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Explanations: How Students Study and Use Examples in Learning to Solve Problems

Abstract: The present paper analyzes the self‐generated explanations (from talk‐aloud protocols) that “Good” and “Poor” students produce while studying worked‐out examples of mechanics problems, and their subsequent reliance on examples during problem solving. We find that “Good” students learn with understanding: They generate many explanations which refine and expand the conditions for the action parts of the example solutions, and relate these actions to principles in the text. These self‐explanations are guided by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
774
3
26

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,620 publications
(844 citation statements)
references
References 21 publications
(17 reference statements)
41
774
3
26
Order By: Relevance
“…One of the factors that seems to be particularly beneficial has been defined as the self-explanation effect (Chi, Bassok, Lewis, Reimann, & Glaser, 1989; see also Reimann & Neubert, 2000;VanLehn, Jones, & Chi, 1992;Wright, 1981), which refers to the idiosyncratic ways individuals explain elements of the examples to themselves during problem solving. For example, VanLehn (1998) observed no difference in the number of self-explanations among successful and unsuccessful solvers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the factors that seems to be particularly beneficial has been defined as the self-explanation effect (Chi, Bassok, Lewis, Reimann, & Glaser, 1989; see also Reimann & Neubert, 2000;VanLehn, Jones, & Chi, 1992;Wright, 1981), which refers to the idiosyncratic ways individuals explain elements of the examples to themselves during problem solving. For example, VanLehn (1998) observed no difference in the number of self-explanations among successful and unsuccessful solvers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the tasks used in most previous studies (Chi, Bassok, et al, 1989;LeFevre & Dixon, 1986) all involved welldefined problems, that is, problems with one correct solution that the participant was expected to attain. Regarding the findings of LeFevre and Dixon (1986), in particular, it is important to examine whether there is a similar preference of participants for examples compared with instructions in ill-defined problems, that is, problems with no one specific correct solution.…”
Section: The Present Study: Overview and Designmentioning
confidence: 99%
“…When students encounter a surprising piece of information their attention is aroused, provoking more intensive processing of the tobe-learned material (i.e., there is a call to explain, to correct and better understand the material). Self-explaining and self-explanation training is also known to improve text comprehension and learning (e.g., Chi, Bassok, Lewis, Reimann & Glaser, 1989;Chi, De Leeuw, Chiu & Lavancher, 1994;Durkin, 2011;Roy & Chi, 2005), particularly for lowknowledge readers (McNamara, 2001;McNamara & Scott, 1999). Self-explanation appears to have a greater impact if there are reliable patterns and consistencies in the material uncovered by the explanations (Williams, Lombrozo & Rehder, 2010); although, conversely, it can be detrimental to learning in some cases if it leads to overgeneralisation (Williams, Lombrozo & Rehder, 2013).…”
Section: Explanation Surprise and Learningmentioning
confidence: 99%
“…In their seminal study on the self-explanation effect, Chi, Bassok, Lewis, Reimann, & Glaser (1989) found that, when studying example exercises in a physics text, the best learners spontaneously explained the material to themselves, providing justifications for each action in a solution sequence. Subsequent studies have shown that prompting for such self-explanations can lead to improved learning outcomes in numerous domains including arithmetic (Calin-Jageman & Ratner, 2005;Rittle-Johnson, 2006;Siegler, 2002), geometry (Aleven & Koedinger, 2002;Wong, Lawson & Keeves, 2003), interest calculations (Renkl, Stark, Gruber & Mandel, 1998), LISP programming (Bielaczyc, Pirolli, & Brown, 1995), argumentation (Schworm & Renkl, 2007), Piagetian number conservation (Siegler, 1995), probability calculation (Große & Renkl, 2003), biology text comprehension (Chi, DeLeeuw, Chiu, & LaVancher, 1994), and balancing beam problems (Pine & Messer, 2000).…”
Section: The Self-explanation Effectmentioning
confidence: 99%
“…Importantly, these differences are associated with divergent learning outcomes (Chi et al, 1989;Chi et al, 1994;Pirolli & Recker, 1994;Renkl, 1997). Successful learners tend to give more principle-based explanations, more frequently consider the goals of operators and procedures, and less frequently show illusions of understanding (see Renkl, 2002 for an effective summary).…”
Section: The Self-explanation Effectmentioning
confidence: 99%